2001
DOI: 10.1080/003655201750153197
|View full text |Cite
|
Sign up to set email alerts
|

Bile-induced Adenosine Triphosphate Depletion and Mucosal Damage During Reflux Esophagitis

Abstract: We propose that mucosal dysfunction, structural damage and leukocyte invasion during hydrochloric acid-induced esophageal injury are exacerbated by bile-induced changes in tissue ATP concentrations during experimental esophageal reflux disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…P2X 3 receptor expression is increased in the enteric plexuses in human irritable bowel syndrome, suggesting a potential role in dysmotility and pain (Yiangou et al, 2001), and the possibility that P2X receptors are potential targets for the drug treatment of irritable bowel syndrome has been raised (Galligan, 2004). Bile induces ATP depletion and contributes to the early mucosal permeability alteration and barrier lesions that occur during experimental esophageal reflux (Szentpali et al, 2001). P2X 3 immunohistochemistry has been demonstrated in aganglionic bowel in Hirschsprung's disease, suggesting that the sensory nerves may form a significant proportion of its hypertrophic innervation ).…”
Section: Gastroenterologymentioning
confidence: 99%
“…P2X 3 receptor expression is increased in the enteric plexuses in human irritable bowel syndrome, suggesting a potential role in dysmotility and pain (Yiangou et al, 2001), and the possibility that P2X receptors are potential targets for the drug treatment of irritable bowel syndrome has been raised (Galligan, 2004). Bile induces ATP depletion and contributes to the early mucosal permeability alteration and barrier lesions that occur during experimental esophageal reflux (Szentpali et al, 2001). P2X 3 immunohistochemistry has been demonstrated in aganglionic bowel in Hirschsprung's disease, suggesting that the sensory nerves may form a significant proportion of its hypertrophic innervation ).…”
Section: Gastroenterologymentioning
confidence: 99%
“…Bile evokes ATP depletion and contributes to the early mucosal permeability alteration and barrier lesions that occur during experimental oesophageal reflux [649]. It has been suggested that purinergic signalling might be involved in achalasia or symptomatic diffuse oesophageal spasm [182,222].…”
Section: Motility Disordersmentioning
confidence: 99%
“…There are some indications that in pathological conditions, such as achalasia or symptomatic diffuse oesophageal spasm, that purinergic signalling might be involved (DiMarino 1974;Fisher and Cohen 1975). In oesophageal reflux disease, bile evoked a significant decrease of oesophageal ATP levels and it was proposed that mucosal damage and dysfunction and leukocyte invasion during acid-induced oesophageal reflux injury is exacerbated by bile-induced changes in tissue ATP (Szentpáli et al 2001). …”
Section: Oesophagusmentioning
confidence: 99%
“…Bile induces ATP depletion and contributes to the early mucosal permeability alteration and barrier lesions that occur during experimental oesophageal reflux (Szentpáli et al 2001). P2Y receptors on smooth muscle and ATP production in myenteric neurons increase in postoperative ileus, probably contributing to delayed colonic transit .…”
Section: Motility Disordersmentioning
confidence: 99%